2002
DOI: 10.2224/sbp.2002.30.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Performance During Stress: Affective Personality, Age, and Regularity of Physical Exercise

Abstract: In order to study the role of stress upon performance as a function of age and personality type, participants were derived from three different occupational categories. Performance ability during stress and health condition of participants were studied through application of the Stroop Color and Word Test, the Stress and Energy Instrument, the Glare Pressure Test and systolic blood pressure measurements -whereas the four different personality types were derived through application of the Positive Affect (PA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(170 citation statements)
references
References 31 publications
10
152
0
4
Order By: Relevance
“…This is consistent with the finding that positive affect is negatively associated with depression (Watson et al, 1988a). By combining high/low positive affect with high/low negative affect, four different types of affective personality have been described (Bood, Archer, & Norlander, 2004;Norlander, Bood, & Archer, 2002). Affective personality types with high negative affect have been shown to report a higher degree of stress and a lower degree of coping and control than those with high positive affect George & Brief, 1992;Spector & O'Connell, 1994).…”
Section: Affective Personality and Stresssupporting
confidence: 75%
“…This is consistent with the finding that positive affect is negatively associated with depression (Watson et al, 1988a). By combining high/low positive affect with high/low negative affect, four different types of affective personality have been described (Bood, Archer, & Norlander, 2004;Norlander, Bood, & Archer, 2002). Affective personality types with high negative affect have been shown to report a higher degree of stress and a lower degree of coping and control than those with high positive affect George & Brief, 1992;Spector & O'Connell, 1994).…”
Section: Affective Personality and Stresssupporting
confidence: 75%
“…Through consideration of these interactions, ref et al [20] developed a 2 x 2 system whereby individuals were categorized into one of four affective profiles: "Selffulfilling" (high PA, low NA), "High affective" (high PA, high NA), "Low affective" (low PA, low NA) and "Self-destructive" (low PA, high NA). Previous studies have shown that "Self-fulfilling" and "Low affective" adults express less stress than the "High affective" and "Selfdestructive" whereas "Self-fulfilling" and "High affective" adults express more energy and lower blood pressure than "Low affective" and "Self-destructive" [19,30].…”
Section: Affective Profilesmentioning
confidence: 96%
“…Subjective well-being consists of cognitive and affective components [18]. The cognitive component concerns individuals' degree of life satisfaction as experienced in relation to an ideal notion [19]. The affective component is expressed through individuals' experiences of positive and negative feelings whereby the subtraction of the latter from the former provides an estimation of 'affect balance' [19].…”
Section: Well-beingmentioning
confidence: 99%
“…In this line of thought, Archer, Garcia and colleagues have developed the affective profile model, which comprises four profiles: self-destructive (low positive affect, high negative affect), high affective (high positive affect, high negative affect), low affective (low positive affect, low negative affect), and self-fulfilling (high positive affect, low negative affect) [17][18][19][20][21][22][23][24][25]. These studies have shown that individuals' levels of energy and optimism are higher among those with a selffulfilling profile than among individuals with any of the other three affective profiles [20].…”
Section: Introductionmentioning
confidence: 99%